ANALISIS SOSIOLEK BAHASA DAYAK POMPANKNG DIALEK BEKIDOH PADA MAHASISWA UNIVERSITAS PGRI PONTIANAK - Fitri Wulansari; Dominika Emi; Liska Indah Erlina; Maria Monika Beo; Putri Dayanti; Herlina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study examines the variation of the Dayak Pompakng language, specifically the Bekidoh dialect, among students of Universitas PGRI Pontianak. Language as a reflection of cultural identity develops dynamically and produces variations influenced by social factors, particularly in the form of sociolects. This research aims to analyze language variation based on levels of formality, namely casual and intimate variations used by students. The method employed is descriptive qualitative. Data collection techniques include observation, participation, interview, recording, and note-taking. The results show variations in word forms such as “əŋredʒa–ŋredʒo,” “ŋai–ŋae,” “boraŋkat–ijoh,” “ŋokɪh–kokɪh,” and “tonɪʔ–labʊʔ,” which have the same meanings but differ in usage according to social context. Casual variation is used in informal situations without requiring close relationships, while intimate variation is used in close social relationships. These findings indicate that language variation reflects patterns of social interaction and plays an important role in maintaining regional languages as cultural identity.